Chemostratigraphy of Sediments in Benin West -1, Benin Flank: Paleoenvironmental Implications (Journal of Scientific Research, 2016)
Chemostratigraphical study was carried out on sediments of Benin west -1 well in order to understand their paleoenvironmental   setting and geochemical zonations. Six chemozones (CHM 1, CHM 2, CHM 3, CHM 4, CHM 5 and CHM 6) were recognized in the stratigraphic column.  Sedimentological attributes and maxima peaks and / or fluctuating trends of Zn, SiO2, K2O, Sr  adjudged CHM 3 zone as a potential lowstand systems tract.  Synergy of sedimentological and chemostratigraphical fingerprints suggests a marine to distributary channel environment of deposition.